Phenomenological Insights into the Integration of Media and Technology in Early Childhood Learning: Perspectives of Teachers and Parents - Saona, Saona (Sekolah Tinggi Agama Islam Kuningan, 2024)
Background: The integration of media and technology in early childhood education has grown rapidly, particularly after the COVID-19 pandemic. Despite this increased use, there is limited understanding of how educators and parents experience and perceive this integration in early childhood learning environments.Objective: This phenomenological study investigates the lived experiences of 52 participants (28 early childhood teachers and 24 parents) on technology integration for children aged 3-6 years, focusing on their perspectives and challenges.Method: Over 10 months, data were gathered via semi-structured interviews, focus groups, and reflective journals. Analysis followed van Manen’s phenomenological approach to capture participants' experiences.Findings and Implications: Four themes emerged: (1) Balancing Benefits and Concerns, (2) Parent-Teacher Communication and Collaboration, (3) Digital Literacy and 21st Century Skills Development, and (4) Implementation Challenges and Support Needs. Stakeholders highlighted diverse views on technology's pros and cons. Effective integration demands educator-family partnerships, professional development, age-appropriate digital citizenship education, and supportive policies for developmentally appropriate practices.Conclusion: Successful technology integration hinges on teacher-parent collaboration, targeted training, and balanced policies. Future research should assess impacts on learning outcomes.